A comparison of rural–urban differences in out-of-pocket expenses among older Mexicans with diabetes - Rojas Alvarez, Alfonso; Vazquez, Christian E.; Lopez-Ortega, Mariana; Angel, Jacqueline L. (Frontiers in Public Health, 2022)
Objective To compare total out-of-pocket expenses for physician visits and medications among older adults living with diabetes in Mexico from urban, semi-urban, and rural areas. Methods The sample included 2,398 Mexicans aged 65 years and older with self-reported diabetes from the 2018 Mexican Health and Aging Study. Out-of-pocket expenses for physician visits and medications were regressed on locality, controlling for several factors. Results The profile of those with higher out-of-pocket medication expenditures included rural localities, higher education, unmarried, depressive symptoms, participation in Seguro Popular, and lacking insurance. In the multivariate analysis, rural older adults with diabetes paid a higher amount in medication expenditures compared with other localities. Conclusion Differences in locality are closely tied to the effective implementation of Seguro Popular. Although this program has improved access to care, participants have higher out-of-pocket expenditures for medications than those on employer-based plans across all localities. Among all groups, the uninsured bare the highest burden of expenditures, highlighting a continued need to address health inequities for the most underserved populations.